The judgment - Coughlin, William J. (William Jeremiah) (New York : St. Martin's Paperbacks, 1999)
Pulled into the two very different cases, Charley faces the heat of a perplexing serial murder investigation and the heavy hitters of the Motor City's inner circle. Interviewing witnesses, putting together clues, Charley Sloan, a man who has been at the bottom and at the top, is about to uncover the explosive difference between true innocence-and the most dangerous guilt of all.
National College of Business and Arts
Keywords: Serial murders -- Fiction; Detective and mystery fiction